2015
DOI: 10.1002/ptr.5365
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cytochrome P450 Activity by 18β‐Glycyrrhetic Acid and its Consequence on Buspirone Pharmacokinetics in Rats

Abstract: The aim of this study was to elucidate the inhibition mechanism of 18β-glycyrrhetic acid (GLY) on cytochrome P450 (CYP) activity and in vivo pharmacokinetic consequences of single GLY dose in rats. An in vitro CYP inhibition study in rat liver microsomes (RLM) was conducted using probe substrates for CYPs. Then, an in vivo pharmacokinetics of intravenous and oral buspirone (BUS), a probe substrate for CYP3A, was studied with the concurrent administration of oral GLY in rats. In the in vitro CYP inhibition stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Plants have for a very long time, formed the basis of sophisticated traditional medicine systems that have been in existence for thousands of years, and continue to provide mankind with new remedies. They have gained a significant increase in popularity, as complementary and alternative medicines for the prevention and treatment of different infectious and non-infectious diseases in human therapy (Kim et al, 2015;Gurib-Fakim, 2006). According to the literature review data, natural products and their derivatives, represent 50%e80% of all the drugs in clinical use in the world (Sen and Samanta, 2015;Petrovska, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Plants have for a very long time, formed the basis of sophisticated traditional medicine systems that have been in existence for thousands of years, and continue to provide mankind with new remedies. They have gained a significant increase in popularity, as complementary and alternative medicines for the prevention and treatment of different infectious and non-infectious diseases in human therapy (Kim et al, 2015;Gurib-Fakim, 2006). According to the literature review data, natural products and their derivatives, represent 50%e80% of all the drugs in clinical use in the world (Sen and Samanta, 2015;Petrovska, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the effects of 1,25(OH) 2 D 3 on the in vivo fate of a CYP3A substrate drug in biological systems, we selected buspirone, an anxiolytic drug, that is metabolized primarily via the rat and human CYP3A subfamily (Kim et al, 2016). The intravenous and oral doses of buspirone were selected based on our previous studies Kim, Cho, Kim, Kim, & Yoon, 2015). Buspirone administered intravenously is known to be eliminated primarily via hepatic metabolism in rats and humans (Gammans, Mayol, & LaBudde, 1986 (Table 3) and rat hepatic blood flow rate (i.e., 50-80 mL/min/kg) (Yoon et al, 2012).…”
mentioning
confidence: 99%
“…Although hepatic metabolism mediated by CYP3A4 and CYP3A5 is well recognized as a major elimination pathway of DUT in humans [6,7], little information has been available as to the hepatic CYPs involved in the metabolism of DUT in rats. The in vitro microsomal metabolism data presented in this study revealed that the metabolism of DUT was markedly reduced by KET, a potent inhibitor of CYP3A in rats and humans ( Figures 6B and 7B) [26,27]. This result indicates that CYP3A plays a significant role in the hepatic metabolism of DUT in rats and humans.…”
Section: Discussionmentioning
confidence: 51%